PHYSICAL AND MECHANICAL PROPERTIES OF Eucalyptus urophylla - Scanavacca Júnior, Laerte; Garcia, José Nivaldo (REVISTA DE AGRICULTURA, 2023)
Eucalyptus urophylla is one of the most planted species in the world and in Brazil for presenting excellent productivity, good adaptability to the most varied types of soil and climate and wide application. The experiment was installed in randomized blocks with four replications, linear plots with six plants in a 3 x 2 m spacing. In this test, 21 progenies were selected in three replications, to evaluate the physical (basic density and shrinkage) and mechanical properties (shear, compression, modulus of elasticity and rupture) of the wood. There was no statistical difference between the progenies for the characteristics evaluated because it was juvenile wood. The basic density showed a positive correlation with the radial and volumetric shrinkage and a negative correlation with the shrinkage index. There is no correlation of DBH with the physical or mechanical properties of wood. The values obtained were low but with the potential to increase.